2016
DOI: 10.1165/rcmb.2016-0063ps
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Modeling of Obese Lung Disease. Insights and Caveats

Abstract: As the obesity epidemic has worsened, its impact on lung health and disease has become progressively evident. The interactions between obesity and the accompanying metabolic syndrome and diseases such as asthma, pneumonia, and acute respiratory distress syndrome (ARDS) have proven complex and often counterintuitive in human studies. Hence, there is a growing need for relevant experimental approaches to understand the interactions between obesity and the lung. To this end, researchers have increasingly exploite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 72 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…To further investigate the relative importance of obesity versus increased fat intake specifically to the increased susceptibility to hyperoxia, we subjected B6.Cg-Lep ob /J (ob/ob) mice and heterozygous controls (ob/+) to 48 hours of hyperoxia. Lack of leptin in these mice leads to marked early-onset obesity, insulin resistance, and more marked hyperglycemia than the high-fat diet-induced obesity model (28,29). As expected, at 13 weeks of age ob/ob mice had significantly increased weight compared with their heterozygous littermates (53.2 ± 1.9 g vs. 30.9 ± 0.5 g, P < 0.0001, Supplemental Figure 2A).…”
Section: Twelve Weeks Of High-fat Diet Results In Weight Gain and Sigsupporting
confidence: 62%
See 1 more Smart Citation
“…To further investigate the relative importance of obesity versus increased fat intake specifically to the increased susceptibility to hyperoxia, we subjected B6.Cg-Lep ob /J (ob/ob) mice and heterozygous controls (ob/+) to 48 hours of hyperoxia. Lack of leptin in these mice leads to marked early-onset obesity, insulin resistance, and more marked hyperglycemia than the high-fat diet-induced obesity model (28,29). As expected, at 13 weeks of age ob/ob mice had significantly increased weight compared with their heterozygous littermates (53.2 ± 1.9 g vs. 30.9 ± 0.5 g, P < 0.0001, Supplemental Figure 2A).…”
Section: Twelve Weeks Of High-fat Diet Results In Weight Gain and Sigsupporting
confidence: 62%
“…on different cell types (28). Wilson et al reported that consumption of a high-fat diet protected mice in terms of alveolar permeability from ventilator-induced lung injury (VILI) using large tidal volumes, independent of leukocyte recruitment and intra-alveolar inflammatory cytokines (41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, others have reported differences in the impact of obesity on bacterial pneumonia depending on the type of obese mice used [34]. Db/db are more hyperglycemic than mice with DIO and marked obesity develops much more rapidly in db/db than in mice with DIO [35]. Db/ db mice are obese because they lack the longform of the receptor for leptin, a satiety hormone expressed in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A specific role for leptin is further supported by the observation of no adverse effects on lung defense in a leptin-independent mouse model of obesity (307). The precise role of leptin is complicated by indirect metabolic consequences of its manipulation and the widespread physiological impacts of obesity (479). Adiponectin is another adipokine with inflammation-regulating properties that may influence pulmonary immune resistance.…”
Section: Fatmentioning
confidence: 99%